Changes in client functioning during treatment at a secondary stage addiction facility: an analysis of case records - Hazell, Nic (Department of Psychology, 2014)
Recent findings indicate that South Africa and, in particular, the Western Cape has some of the highest prevalence of substance use disorders and substance related problems in the world. Further, in the past decade, the prevalence of poly-substance use in South Africa has grown considerably. The high prevalence of substance use disorders and related problems in the Western Cape relative to an already significant national problem highlights the importance of local research on the effective treatment of substance use disorders. While there are outcome studies supporting the effectiveness of various addiction treatment models, and much is known about the various stages of intervention at addiction treatment facilities, little is known about the processes and mechanisms of addiction treatment and recovery. Various authors have proposed that researching patient progress through treatment is essential to growing our knowledge, improving treatments and generalising them to other settings. This study aimed to investigate client case files at a secondary stage addiction treatment facility in Cape Town to explore whether there were any discernible patterns in clients' functioning across different stages of treatment. The research took the form of a case study that used thematic analysis to discern patterns in qualitative data regarding reported observations of client's behaviours, cognitions, affects and physical states at different stages of addiction treatment. Comparisons were also made between the observations of clients with Axis II personality traits and those without Axis II personality traits, and between clients recovering from stimulant addiction and those recovering from non-stimulant addiction. The participants comprised a sample of 33 clients of a secondary stage addiction treatment facility in Cape Town, South Africa. Analysis yielded a number of possible patterns in the distribution of themes across time-points, some of which resonated with previous research, particularly regarding second order change, but also regarding Protracted Withdrawal Syndrome and 'The Wall'. The comparative analysis indicated that there might be both similarities and differences between subgroups of clients that may shed light on the use of matching hypotheses in the context of addiction treatment.